Regent School of Economics a Case Study - Padmasiri, K. Don Ranjith (1999)
Private education is the education provided to pupils by private educational intuitions. They are non-government aided intuitions and are fully funded by the private sector. Private colleges fall under one of the categories of private education, the others being - private universities, private kindergartens and private schools. The establishment, management and operation of private educational institutions in Malaysia are governed by the following Acts: • Education Act 1996 • Private Higher Educational Institutions Act 1996 • The National Council on Higher Education Act 1996 • The National Accreditation Board Act 1996 Private education in Malaysia started in 1950s, mainly as a gateway for students who cannot enter Government schools to obtain their basic certificates. Only in 1970s was there a shift of roles and functions of private education system, where more emphasis was placed on pre-university courses. The 1980s saw another significant change, whereby private colleges provided tertiary education, particularly, in conducting courses leading to foreign qualifications at certificate, diploma and professional levels. During this period, private colleges provided an alternative access to university education for those who were unable to gain entry into Government's higher education intuitions. It should be noted that until 1998, no private college was allowed to fully conduct degree courses in Malaysia.